2011
DOI: 10.1039/c0cp01612h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-supported Pt⁁Ag nanostructures as cathode catalysts for oxygen reduction reaction

Abstract: Pt(m)^Ag nanostructures (m being the atomic Pt/Ag ratio, m = 0.1-0.6) were prepared by reflux citrate reduction of PtCl(6)(2-) ions in aqueous solution containing colloidal Ag (6.3 ± 3.9 nm). A distinct alloying of Pt with Ag was detected due to an involvement of the galvanic replacement reaction between PtCl(6)(2-) and metallic Ag colloids. The nanostructure transformed from a structure with an Ag-core and an alloyed PtAg-shell to a hollow PtAg alloy structure with the increase in m. Compared to a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 36 publications
(60 reference statements)
5
48
0
Order By: Relevance
“…Incomplete extinguishing of the plasmon band was not totally unexpected, for two reasons. Firstly, Feng et al have reported that the plasmon band is not completely extinguished in Pt-shell on Ag-core structures having low levels (<0.2 mol fraction) of Pt on the surface of the Ag core [15]. Secondly, trace Ag-ion probably remained in solution and was co-deposited during reductive deposition of Pt and Pd.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Incomplete extinguishing of the plasmon band was not totally unexpected, for two reasons. Firstly, Feng et al have reported that the plasmon band is not completely extinguished in Pt-shell on Ag-core structures having low levels (<0.2 mol fraction) of Pt on the surface of the Ag core [15]. Secondly, trace Ag-ion probably remained in solution and was co-deposited during reductive deposition of Pt and Pd.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%
“…Although PtAg and PdAg systems have been reported to show good catalytic properties toward the ORR [15,16], surprisingly few studies have focused on the use of an Ag core, and to date, there has been no report of a study using an Ag nanoparticle with a PtPd-enriched surface (Ag@PtPd) as an ORR catalyst. Here we report the synthesis of an Ag-rich nanoparticle with a PtPd-enriched surface (Ag@Pt 0.1 Pd 0.1 ) made by reduction of Ag ions in solution to form Ag nanoparticle and then reduction of Pt and Pd ions in solution using sodium citrate as a surfactant and sodium borohydride as a reducing reagent [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This agglomeration leads to a significant 4 loss of the effective surface area for GNs in the solid state, which can restrict their application [24,25]. Therefore, construction of the GNs with large surface area in their solid state is of dominant importance to advance the applications of GNs [19,26,27]. Decorating of the GNs by nobel metal nanoparticles, like Pt and Au, increases the interlayer distance of the GNs and inhibits the adhesion of the resulting GNs in their dry state, which maintain their large surface area [27].…”
Section: Introductionmentioning
confidence: 98%
“…As a result, the combination of alloying and porous structure can be expected to be a promising candidate for the development of efficient ORR electrocatalysts, which has been proved by several very recent successful examples [9,10,15,16,18]. Hong et al prepared Pd-Pt alloy hollow nanostructures by sacrificial template method [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the shape and morphology of nanocrystals are also of great importance in the development of ORR catalysts. Therein, porous nanocatalysts [9][10][11][12][13][14][15][16] are attracting more and more attention, because the porous structure gives birth to high surface area to volume ratios and creates a confined reaction environment that improves the reaction kinetics [14,15]. Moreover, the non-zero dimensional nanostructure makes the porous nanocrystals less vulnerable to dissolution, Ostwald ripening, and aggregation during * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%